Effect of Addition of EM4 and Molasses Bioactivator in Making Liquid Organic Fertilizer from Balinese Restaurant Waste - Adi, I Putu Cahya Windu; Wirawan, I Putu Surya; Madrini, Ida Ayu Gede Bintang (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Liquid organic fertilizer is a type of fertilizer made from the utilization of organic waste. Food waste used in the process of making liquid organic fertilizer includes vegetables, leftover rice, onion peel, and fruit residue. The purpose of this study was to obtain the effect of using EM4 and molasses bioactivator in the manufacture of liquid organic fertilizer. The method used for water content analysis is the gravimetric method (AOAC 2016). From the results of research that has been done that the use of molasses and EM4 does not cause a significant effect on temperature and pH. From the results of field research, the average temperature obtained from three replications is 27.8ºC and the resulting pH value is 7.49 at the beginning of the fermentation. In the analysis of NPK levels, the role of the use of molasses and EM4 is very influential, where each produces a value of 0.12%, 0.042% , 0.022% which is the highest value for NPK. The results of the analysis of the water content of the material get a value of 47.73%. The results of the analysis of the C/N ratio showed that the C-Organic value was higher than the N-total value. The colors produced from leachate materials are very diverse, due to variations in the raw materials used. The use of molasses and EM4 bioactivator had no effect on temperature and pH but did have a significant effect on NPK levels.